Faith, Custom, and Village Authority: The Historical Transformation of Muro Nggeteq in East Lombok, 1960-1990 - Dhea Himawati; Abdul Rasyad; Syahrul Amar (Universitas Hamzanwadi, 2024)
Muro Nggeteq was a premarital adat gama ritual in Pengadangan Village, East Lombok, that combined Islamic repentance, customary examination, and village administration. This article reconstructs its historical transformation between 1960 and 1990 and explains why the ritual remained strong before 1975 but declined thereafter. The study used the historical method through heuristics, source criticism, interpretation, and historiography. Sources included interviews with customary leaders, religious figures, village officials, community elders, and a young cultural activist; written repentance formulas and village records; material objects; and field documentation. The findings show that the ritual's agrarian terms formed a moral metaphor: muro meant guarding a relationship, while nggeteq meant admitting prohibited premarital conduct. Its stages - betaubat, taklik, and a mosque examination - represented a triadic normative order of Islamic, customary, and governmental law. Under Seneng, Iradim, and Mamiq Rul (1960-1975), these authorities were institutionally aligned, making the ritual socially obligatory. Under Sukarma (1975-1990), procedure was simplified, governmental enforcement weakened, and expanding fiqh interpretation separated religious requirements from inherited ceremonial forms. By 1991, the integrated ritual had disappeared. The article concludes that cultural continuity depended on institutional cooperation and shared interpretation. Contemporary revitalization should retain premarital education, responsibility, and inter-institutional cooperation while excluding corporal punishment, coercion, and public shaming.